2010
DOI: 10.4037/ajcc2010590
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morbidity and Mortality Conferences on Analysis of Mortality and Critical Events in Intensive Care Practice

Abstract: Background Morbidity and mortality conferences are a tool for evaluating care management, but they lack a precise format for practice in intensive care units. Objectives To evaluate the feasibility and usefulness of regular morbidity and mortality conferences specific to intensive care units for improving quality of care and patient safety. Methods For 1 year, a prospective study was conducted in an 18-bed intensive care unit. Events analyzed included deaths in the unit and 4 adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
68
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 46 publications
0
68
0
17
Order By: Relevance
“…It is observed in the literature that increasing length of hospital stay before the occurrence of adverse events is a known variable (13,16,22) . A French prospective study in an ICU with 18 beds showed that the most serious AE occurred in elderly patients with greater stay and duration of invasive ventilation (13) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is observed in the literature that increasing length of hospital stay before the occurrence of adverse events is a known variable (13,16,22) . A French prospective study in an ICU with 18 beds showed that the most serious AE occurred in elderly patients with greater stay and duration of invasive ventilation (13) .…”
Section: Discussionmentioning
confidence: 99%
“…A French prospective study in an ICU with 18 beds showed that the most serious AE occurred in elderly patients with greater stay and duration of invasive ventilation (13) . Another study that identified AE in medical records in hospitalized elderly from two wards found a significant difference in length of hospital stay between cases where there was event registries (16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Как показывает опыт, обучаемые имеют ограничен-ное представление о том, что происходит с ними, когда они вовлечены в процесс симуляции [8]. Зарубежными исследователями доказано, что наличие визуальных, зву-ковых и тактильных стимулов во время симуляционного обучения, использование видеоповторов и конструктив-ного обсуждения после выполнения задания помогает восприятию новой информации и способствует лучшему запоминанию [9]. Находясь в центре событий, курсанты видят только то, что можно увидеть с точки зрения актив-ного участника, а именно благодаря конструктивному об-суждению после выполненного задания, симуляционный опыт превращается в осознанную практику, которая в итоге помогает обучаемому подготовиться к той или иной ситуации у пациентки.…”
Section: Discussionunclassified